Anti-drug Antibodies Against a Novel Humanized Anti-CD20 Antibody Impair Its Therapeutic Effect on Primary Biliary Cholangitis in Human CD20- and FcγR-Expressing Mice - Moritoki, Yuki; Tsuneyama, Koichi; Nakamura, Yuka; Kikuchi, Kentaro; Shiota, Akira; Ohsugi, Yoshiyuki; Lian, Zhe-Xiong; Zhang, Weici; Yang, Guo-Xiang; Ueki, Shigeharu; Takeda, Masahide; Omokawa, Ayumi; et al. (Frontiers in Immunology, 2018)
There is considerable interest in expanding B cell-targeted therapies in human autoimmune diseases. However, clinical trials in human primary biliary cholangitis (PBC) using a chimeric antibody against human CD20 (hCD20) have showed limited efficacy. Two potential explanations for these disappointing results are the appearance of anti-drug antibodies (ADAs) and the high frequency of patients with moderate PBC or patients who had failed ursodeoxycholic acid treatment. Here, we studied a novel humanized IgG1 antibody against hCD20 and explored its efficacy in early stage PBC using a well-defined murine model. We developed a unique murine model consisting of dnTGF-βRII mice expressing hCD20 and human Fcγ receptors (hFcγRs). Beginning at 4–6 weeks of age, equivalent to stage I/II human PBC, female mice were given weekly injections of an anti-hCD20 antibody (TKM-011) or vehicle control, and monitored for liver histology as well as a broad panel of immunological readouts. After 16 weeks’ treatment, we observed a significant reduction in portal inflammation, a decrease in liver-infiltrating mononuclear cells as well as a reduction in liver CD8+ T cells. Importantly, direct correlations between numbers of liver non-B cells and B cells (r=0.7426, p=0.0006) and between numbers of liver memory CD8+ T cells and B cells (r=0.6423, p=0.0054) were apparent. Accompanying these changes was a dramatic reduction in anti-mitochondrial antibodies, interleukin (IL)-12p40 and IL-5, and elevated levels of the anti-inflammatory chemokine CXCL1/KC. In mice that developed ADAs, clinical improvements were less pronounced. Sustained treatment with B cell-targeted therapies may broadly inhibit effector pathways in PBC, but may need to be administered early in the natural history of PBC.